Dihydroisocoumarins produced by Xylaria sp and Penicillium sp., endophytic fungi associated with Piper aduncum and Alibertia macrophylla - Oliveira, Camila M. [UNESP]; Regasini, Luis O. [UNESP]; Silva, Geraldo H.; Pfenning, Ludwig H.; Young, Maria C. M.; Berlinck, Roberto G. S.; Bolzani, Vanderlan da Silva [UNESP]; Araujo, Angela R. [UNESP] (Elsevier B.V., 2011)
The dihydroisocoumarin (3R, 4R)-3,4-dihydro-4,6-dihydroxy-3-methyl-1-oxo-1H-isochromene-5-carboxylic acid (1) was isolated from Xylaria sp., a fungus associated with Piper aduncum (Piperaceae). Additionally, two known compounds, (R)-7-hydroxymellein (2) and (3R, 4R)-4,7-dihydroxymellein (3), were isolated from Penicillium sp. associated to Alibertia macrophylla (Rubiaceae). The structures of all compounds were elucidated by analysis of spectroscopic data. The dihydrocoumarin derivatives 1-3 showed antifungal and acetylcholinesterase (AChE) inhibitory activities in vitro. (C) 2010 Phytochemical Society of Europe. Published by Elsevier B. V. All rights reserved.
Keywords: Dihydroisocoumarins; Endophytic fungi; Bioactive compounds